Repair of mandrels of a continuous mill through the use of adapters - E. V. Zhuravleva; O. M. Lazko; A. N. Shashkov; A. B. Manyakin (Литьë и металлургия)
The article describes the repair of mandrels used on a continuous type PQF mill by using adapters made from billets. The starting materials are the tailstocks that have been taken out of service.The process of repairing the mandrels allows the mandrel to be used in further work until the final regrinding to the last size range of the mandrel diameter.The technological process of repair begins with turning the surface of the mandrel to the required size, grinding the surface, the process of cutting off the rear part of the mandrel, including the threaded connection. After the tailstock part has been cut off, the tailstock section is replaced with a transition piece manufactured in‑house. The adapter is a part with a fine tapered thread on one side, which is intended for connection to the mandrel, and with an internal thread on the other side, which serves to connect the rear part of the mandrel to the tailstock.The provided technology will reduce the cost of purchasing new replacement tools by increasing the life cycle of the mandrel, and will reduce the number of mandrels that have become unusable by restoring the tailstock part.